2012
DOI: 10.3354/meps09777
|View full text |Cite
|
Sign up to set email alerts
|

Feeding habitat of the whale shark Rhincodon typus in the northern Gulf of Mexico determined using species distribution modelling

Abstract: Whale shark Rhincodon typus is a globally distributed species, but there is a lack of knowledge pertaining to their biology, seasonal occurrence, and distribution in the northern Gulf of Mexico (NGOM). Understanding critical habitat for whale sharks is essential on both a regional and global basis for proper management because of their large migratory range. The goal of the present study was to describe the regional distribution of whale shark feeding aggregations in the NGOM by exploiting a presence-only data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 52 publications
4
64
1
5
Order By: Relevance
“…The southern part of the Odisha coast becomes more productive with periodic phytoplankton and ciliate blooms and these were mainly attributed to local coastal upwelling (Choudhury & Panigrahy 1989;Panigrahy & Gouda 1990;Sasamal et al 2005;Mohanty et al 2007;Sahu et al 2016). Chlorophyll a and phytoplankton concentration have been used successfully to predict the seasonal occurrence of these Whale Sharks in the northern Gulf of Mexico (McKinney et al 2012). During the present study fish eggs were found to be dominant in the plankton sample; however, it cannot be ascertained that the abundance of fish eggs might be the reason for the occurrence of the Whale Shark in the region during February-March.…”
contrasting
confidence: 50%
“…The southern part of the Odisha coast becomes more productive with periodic phytoplankton and ciliate blooms and these were mainly attributed to local coastal upwelling (Choudhury & Panigrahy 1989;Panigrahy & Gouda 1990;Sasamal et al 2005;Mohanty et al 2007;Sahu et al 2016). Chlorophyll a and phytoplankton concentration have been used successfully to predict the seasonal occurrence of these Whale Sharks in the northern Gulf of Mexico (McKinney et al 2012). During the present study fish eggs were found to be dominant in the plankton sample; however, it cannot be ascertained that the abundance of fish eggs might be the reason for the occurrence of the Whale Shark in the region during February-March.…”
contrasting
confidence: 50%
“…The dynamic physical processes associated with shelf edges generate upwellings of nutrient-rich water to the surface [15], that can result in localized increases in planktonic biomass [100][102]. A correlation between whale shark distribution and proximity to the shelf edge has been described for the northern GOM [7], [103] and may be related to pulses of productivity associated with these areas.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, sunfish tracked outside the Mediterranean experienced a SST range from 13 to 23 °C. This thermal envelope was found to be warmer for individuals that entered the Mediterranean (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)Figs. 3,4).…”
Section: Environmental Integration Of Sunfish Movementsmentioning
confidence: 96%
“…The aggregation of marine pelagic vertebrates in areas dominated by steep thermal gradients such as tidal and shelf-break fronts, upwelling regions, mesoscale eddies and oceanic fronts has also been documented widely [for review, see 16]. Chlorophyll a was also found to influence the distribution and migration of marine predators such as loggerhead turtles and albacore tuna (Thunnus alalunga) [17] and whale sharks (Rhincodon typus) [18]. Hence, the importance of these oceanographic features is likely due to improved foraging opportunities [19].…”
Section: Open Accessmentioning
confidence: 97%